Genomic DNA restriction endonuclease from Pasteurella multocida isolated from Indonesia, katha strain and reference strains and analysed by PFGE - ., Supar (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Pasteurella multocida strains are the causative disease agents of wide range of domestic and wild animals in Indonesia. The most important serotypes are associated with Hemorrhagic septicaemic (HS) diseases in cattle and buffaloes, cholera in ducks and chickens. The HS disease associated with P. multocia in large ruminants in Indonesia is controled by killed whole cell vaccines produced by the use of P. multocida Katha strains. There is no discriminatory data of the molecular biology technique has been applied to investigate P. multocida isolates from different geographic locations in Indonesia. The purpose of this studies were to observe the genetic diversity among P. multocida isolated from various geograpic locations and compared with Katha vaccine strain and other reference strains. A total samples of 38 isolates and strains of P. multocida were analysed by means of pulsed-field gel electrophoresis (PFGE). Each sample was grown in nutrient broth, cells were separeted by centrifugation. Whole cell pellet was mixed with agarose and then prepared agarose plugs. The genomic DNA of each sample was digested in situ (plug) with either restriction endonuclease of ApaI and/or BamHI. The digested genomic DNA of each sample was analysed by PFGE, the genomic DNA restricted profile of each sample was compared with others. The use of ApaI restriction endonuclease digestion and analysed by PFGE, demonstrated that 34 out of 38 P. multocia samples could be differentiated into 16 ApaI types, whereas based on the BamHI digestion of these samples were differentiated into 20 BamHI types. Genomic DNA restriction pattern of Indonesian P. multocida isolates originated from cattle and buffaloes associated with haemorrhagic septicaemic diseases demonstrated different pattern to those of vaccine Katha strain, poultry strains as well as the reference strains currenly kept at Balitvet Culture Collection (BCC) unit. Two P. multocida isolates derived from ducks with cholera disease showed similar pattern support the previous findings which exhibited similar pathogecity and vaccine protection. The majority of HS causing P. multocida isolates from some provinces in Indonesia belong to ApaI type 1 (7 isolates), six of these isolates belong to BamHI type 1. The BamHI restriction endonuclease digestion demonstrated higher discriminatory than that of ApaI. These restrection endonucleases digestion combined with PFGE analysis were effective for molecullar defferentiation of P. multocida strains and could be applied to other bacterial veterinary pathogens as well as for local isolate vaccine sellection. Â  Key words: Pasteurella multocida, restriction endonuclease analysis, genomic DNA, PFGE